2022
DOI: 10.1136/bmjophth-2021-000867
|View full text |Cite
|
Sign up to set email alerts
|

Persistent reduction of retinal microvascular vessel density in patients with moderate and severe COVID-19 disease

Abstract: ObjectiveThis study aims to analyse the possible recovery or worsening in retinal microvasculature after 8 months in a previously studied COVID-19 cohort.Methods and analysisA cross-sectional case–control study and a prospective longitudinal cohort study. Participants were the subjects of our previous study who re-enrolled for a new examination including a fundus photograph (retinography), an optical coherence tomography (OCT) scan and an OCT angiography. COVID-19 diagnosed patients were divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Notably, we also found no differences when comparing acute COVID-19 patients with a healthy control group [ 16 ]. While some of the previous studies are in line with our results [ 17 , 18 ], a decreased VD and an enlarged FAZ area were reported [ 18 , 19 , 20 , 21 , 46 ] and the observed differences were either stable [ 47 ] or more pronounced after a 3–8 month follow-up [ 21 , 21 , 22 , 23 , 23 ]. However, none of the studies reported any macroscopic changes on OCTA images, suggestive of either thromboembolisms or ischemia.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, we also found no differences when comparing acute COVID-19 patients with a healthy control group [ 16 ]. While some of the previous studies are in line with our results [ 17 , 18 ], a decreased VD and an enlarged FAZ area were reported [ 18 , 19 , 20 , 21 , 46 ] and the observed differences were either stable [ 47 ] or more pronounced after a 3–8 month follow-up [ 21 , 21 , 22 , 23 , 23 ]. However, none of the studies reported any macroscopic changes on OCTA images, suggestive of either thromboembolisms or ischemia.…”
Section: Discussionsupporting
confidence: 93%
“…Their control cohort consisted of 27 age- and sex-matched patients. Garcia et al [ 47 ] re-imaged the same cohort of patients imaged in Zapata et al's study 8 months after the baseline visit. This study provides evidence of lower central retinal VD persistence in patients with moderate and severe COVID-19 pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…46 Differences in vascular density between patients with COVID-19 and healthy controls have been observed, and these may last for months postinfection. 47 Some research shows reduced vascular density in both superficial and deep capillary plexuses (DCP) at foveal and parafoveal levels among patients with COVID-19, whereas other studies find these changes mainly in peripheral areas. Some research also shows an enlarged foveal avascular zone and increased choroidal capillary plexus blood flow, likely due to hypoxia and inflammation-induced vasodilation.…”
Section: Microvascular Changesmentioning
confidence: 99%
“…These changes may be attributed to the infection and systemic conditions like hypertension or medical treatments 46 . Differences in vascular density between patients with COVID-19 and healthy controls have been observed, and these may last for months postinfection 47 . Some research shows reduced vascular density in both superficial and deep capillary plexuses (DCP) at foveal and parafoveal levels among patients with COVID-19, whereas other studies find these changes mainly in peripheral areas.…”
Section: Vitreoretinal Manifestations Of Coronavirus Disease 2019mentioning
confidence: 99%